Território e sindicatos em Ourinhos-SP: estudo a partir da imprensa sindical - Barros, Thiago Pereira de [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The present work has as main object to study the territorialization of the press union in Ourinhos, since the character of potential resistance that communication takes the offensive against employer, serving to some extent the demands of the working class. And besides, we analyzed the potential interaction with workers in the information, dialogue, preserving the memory and the construction of collective identity. For this purpose we analyze the speeches in the press union ourinhense, how it is organized and what it reveals about the political and ideological positions of the union. This proposal is consistent with the attempts of rapprochement between labor studies and Geography, with the definitions of the spatial practices of capital and their relations with workers, we can see in the press union bias or collaboration of resistance to capitalist development, leading into account the complexities and nuances that involve such radically opposed positions on territorial unions in Ourinhos

O presente trabalho tem como objetivo principal estudar a territorialização da imprensa sindical em Ourinhos-SP, visto o caráter de comunicação de resistência que esta pode produzir frente à ofensiva patronal, atendendo em alguma medida às demandas da classe trabalhadora. E, além disso, analisou-se a interatividade potencial com os trabalhadores quanto à informação, diálogo e construção da identidade coletiva. Para tanto analisamos os discursos presentes na imprensa sindical ourinhense, a forma como é organizada e o que revela quanto aos posicionamentos político-ideológicos do sindicato. Tal proposta coaduna-se com as tentativas de aproximação entre os estudos do trabalho e a Geografia, com a tessitura dos liames definidores das práticas espaciais do capital e suas relações com os trabalhadores, na medida em que através da imprensa sindical podemos constatar o viés de resistência ou colaboração para o desenvolvimento capitalista, levando-se em consideração as complexidades e nuances que envolvem tais posicionamentos radicalmente contrários na territorialização dos sindicatos em Ourinhos
Keywords: Sindicatos; Imprensa trabalhista; Trabalho